Projeto - A beleza na reutilização - Souza, Aracelly de Oliveira Franco de; Siqueira, Liliane Rosa; Siqueira, Wania Rosa; Lima, Ceonora Gomes; Silvério, Agda Rodrigues Rios; Lima, Eliene Xavier de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF